Iatrogenic metacarpal fracture after K-wire fixation: A case report and prevention - Gu, Ja Hea (Int J Surg Case Rep, 2019)
INTRODUCTION: Iatrogenic fractures after failed K-wire fixation in the management of a carpometacarpal (CMC) joint fracture-dislocation have not yet been reported (Hsu et al., 2011). We present a case of K-wire-related complication in the management of a CMC joint fracture-dislocation and highlight the importance of planning K-wire placement and minimizing the number of K-wire passes. PRESENTATION OF CASE: After beating his hand against a wall, a 22-year-old patient visited our clinic complaining of a swollen and painful wrist. Following our protocol, reduction and K-wire fixation was planned. During these procedures, the resident of our team made several attempts to insert transfixation pins and radiologic finding demonstrated incorrect placement of the K-wire track. The patient visited the outpatient clinic at 5 weeks postoperatively then we removed the K-wires and began mobilization. Two weeks later, the patient came back with acute onset of pain and swelling at the 5th metacarpal area. DISCUSSION: Stahl and Schwartz reported that 27.8 % of complications related K-wire were due to technical failure and 90 % of technical failure were caused by hospital residents. Well-established guidelines and supervision by a highly experienced surgeon is likely to reduce the rate of technical failure. Multiple passes of the K-wire have resulted in blunting of the K-wire and subsequent heat generation then lead to subsequent loosening and loss of fixation. CONCLUSION: Preoperative planning, marking the K-wire route, and appropriate K-wire thickness minimize such complications. Patients should be informed that following K-wire removal, the residual holes could be subject to stress risers.